"The Heritage of the People Closed Against Them:" Class, Environment, and the Shaping of Burlington Beach, 1870s–1980s - Cruikshank, Ken; Bouchier, Nancy (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2001)
Following serious flooding in the 1970s, Hamilton, Ontario politicians and planners sought to transform the Burlington Beach area into a recreational parkland. This dream was not a new one. One hundred years earlier, Hamilton social and political leaders also had envisioned the area, with its fine lakeside beaches and scenic bayside shoreline, as a recreational area. In the 1870s they consciously took control of this small fishing and farming community, contending that the area should be preserved for "the health and welfare of the people." The people, it turned out, were well-to-do residents eager to create a private summer refuge from the heat, dirt, and people of an industrializing city. Within a generation, however, city residents of more modest means challenged "the aristocratic seclusion" of the beach, and successfully struggled to create beaches and parks that would be open to a wider public. Not for long. Within another generation, the beach strip ceased to be an attractive recreational area. Working Hamiltonians saw it as a site for relatively inexpensive housing, and expanded the private residential community. They helped to build the unique community that would frustrate a new generation of recreational promoters in the 1970s. Residents of the community had inherited the private property claims and rights that city politicians had fostered in the area since the 1870s, and forced politicians and planners of the 1970s and 1980s to adopt an alternative vision of the beach strip.This paper traces the struggle of social groups to create and enforce their vision of the beach, a struggle that was in turn shaped by the particular urban and industrial development of the Hamilton region between the 1870s and 1980s. The environmental transformation of this strip of land, and the degradation of the waters surrounding it, affected the ways in which social groups perceived the beach and the purposes it might serve. Its history provides insights into the interaction of leisure, class, and the environment in an industrial city.